Market risk management and its impact on the stability of the Peruvian Banking System - Hidalgo Tupia, Manuel Alberto (2020)
Objective: Determine the level of impact of Market Risk Management in accordance with the risk management standards of the Superintendency of Banking, Insurance (SBS) and AFP on the stability of Peruvian banking companies. Method: The research was non-experimental, it used a transverse design, using documentary analysis and survey as information gathering tools. Results: They showed a significant relationship between the application of the Market Risk Management System (SGRM) and the stability of the banking system in Peru, showed, differences in the impact of each component of the SGRM. Conclusions: It was determined that the implementation of the SGRM positively influences the stability of the Peruvian Banking System, indicating factors that may affect that influence.